2005
DOI: 10.1152/ajpgi.00243.2005
|View full text |Cite
|
Sign up to set email alerts
|

1α,25-Dihydroxyvitamin D3upregulates FGF23 gene expression in bone: the final link in a renal-gastrointestinal-skeletal axis that controls phosphate transport

Abstract: Fibroblast growth factor (FGF)23 is a phosphaturic hormone that decreases circulating 1alpha,25-dihydroxyvitamin D(3) [1,25(OH)(2)D(3)] and elicits hypophosphatemia, both of which contribute to rickets/osteomalacia. It has been shown recently that serum FGF23 increases after treatment with renal 1,25(OH)(2)D(3) hormone, suggesting that 1,25(OH)(2)D(3) negatively feedback controls its levels by inducing FGF23. To establish the tissue of origin and the molecular mechanism by which 1,25(OH)(2)D(3) increases circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
259
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(275 citation statements)
references
References 33 publications
11
259
1
3
Order By: Relevance
“…[40][41][42][43] Therefore, UMR-106 cells are thought to possess surrogate characteristics of the osteoblast/osteocyte lineage. The cells were treated with 10, 50 and 100 ng ml À 1 recombinant DMP1 for 24 h. As shown in Figure 3a, DMP1 significantly reduced the gene expression of fgf23.…”
Section: Direct Regulation Of Fgf23 By Dmp1mentioning
confidence: 99%
“…[40][41][42][43] Therefore, UMR-106 cells are thought to possess surrogate characteristics of the osteoblast/osteocyte lineage. The cells were treated with 10, 50 and 100 ng ml À 1 recombinant DMP1 for 24 h. As shown in Figure 3a, DMP1 significantly reduced the gene expression of fgf23.…”
Section: Direct Regulation Of Fgf23 By Dmp1mentioning
confidence: 99%
“…The wide-ranging activity of klotho raises the possibility that regulation of Ca and phosphate metabolism is an Urinary P ↑ Urinary Ca ↓ essential feature of many systems of the body, not just those connected with the skeleton. Further information on this area of discussion is available (1,20,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) .…”
Section: Low Serum Calciummentioning
confidence: 99%
“…3). Considering the fact that VDR-null mice also displayed undetectable FGF23 levels [32,33], and 1,25(OH) 2 D stimulats FGF23 expression [34][35][36], the VDR-vitamin D system definitively plays an important role in FGF23 regulation. It has been shown that FGF23-null mice display hyperphosphatemia, hypercalcemia, elevated serum 1,25(OH) 2 D, and vascular calcification of the kidneys [37].…”
Section: Discussionmentioning
confidence: 99%